Consumer motivation and luxury consumption: Testing moderating effects. (January 2019) - Shao, Wei; Grace, Debra; Ross, Mitchell
Abstract: Despite the growth of luxury markets during the last decade, luxury brand management is facing tremendous changes and challenges. In previous research, the focus has largely been on the appeal of luxury brands to represent status and prestige. However, this study argues that luxury consumption is highly individualistic and is a means through which consumers pursue personal goals. This research examines the influence of consumer goal attainment (extrinsic and intrinsic) on intention to purchase luxury products (explicitly versus subtly marked). Study 1 examines the moderating role of consumer need for uniqueness. Study 2 examines the moderating role of self-monitoring of expressive behaviour. This research resulted in three major findings. Firstly, this research shows that all respondents were more willing to buy a luxury product when it was subtly marked rather than explicitly marked. Secondly, extrinsically motivated respondents showed a greater preference for the luxury product, irrespective of signal type, than did intrinsically motivated respondents. Thirdly, for the intrinsically motivated respondents, Study 1 showed that individuals whose needs for uniqueness is high are predisposed to inconspicuous consumption. This effect was observed for respondents who were intrinsically motivated, but not for those who were extrinsically motivated. Study 2 demonstrated that low self-monitors were more disposed to inconspicuous consumption. Again, this effect was observed for respondents who were intrinsically motivated, but not for those who were extrinsically motivated. Theoretical and practical implications are discussed.